The Effects of Linguistic Imperialism in the EFL Classroom - Romero Pinto, Mary Addison (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractThis article attempts to analyze and reveal the effects of linguistic imperialism in English Foreign Language Teaching and Learning.First, it will address global English language as the global standard language, that has imposed American and British methodologyand resources in the entire world, and this universal language will also be studied as a symbol of power over the foreign language policies in Colombia. Secondly, the article deals with the fact that the linguisticimperialism controls from beginning to end in “Estándares básicos de competencias en lenguas xtranjeras: inglés. Formar en lenguasextranjeras: ¡el reto!” (Basic standards for competences in foreign languages, English. Teaching in foreign languages: The challenge!). It means that the Anglo-American hegemony sets the parameters of how, what, and to whom perform an EFL class. Lastly, conclusions will be drawn to stimulate EFL teachers to work on autonomous EFL teaching. Namely EFL teachers should focus on intercultural communication and competence, instead of fostering the spreading of English as the global language.Keywords: Linguistic Imperialism, EFL classroom: teaching and learning, and Colombian bilingualism program.